درجة مساهمة التكوين المهني (نمط الحضوري) في تعزيز الثقافة المقاولاتية لدى متربصي المعهد الوطني المتخصص في التكوين المهني المسيلة 02 - رياض بوختالة; اشراف: بوزناد سميرة (جامعة محمد بوضياف المسيلة, 2025)
هدفت الدراسة الحالية إلى معرفة درجة مساهمة التكوين المهني:- المناخ التنظيمي للتكوين المهني- الأنشطة المرافقة للتكوين المهني- التربصات التطبيقية في الوسط المهني (نمط الحضوري) في تعزيز الثقافة المقاولاتية ، ولتحقيق أهداف الدراسة ذات الصيغة الوصفية صمم الباحث استبيان لهذا، وقد بلغت عينة الدراسة (95) متربص من تخصصات مختلفة على مستوى المعهد الوطني المتخصص في التكوين المهني المسيلة02، وتوصلت الدراسة إلى النتائج التالية: - درجة مساهمة المناخ التنظيمي للتكوين المهني (نمط الحضوري) في تعزيز الثقافة المقاولاتية لدى متربصي المعهد الوطني المتخصص في التكوين المهني المسيلة 02 متوسطة. - درجة مساهمة الأنشطة المرافقة للتكوين المهني (نمط الحضوري) في تعزيز الثقافة المقاولاتية لدى متربصي المعهد الوطني المتخصص في التكوين المهني المسيلة 02 عالية. - درجة مساهمة التربصات التطبيقية في الوسط المهني (نمط الحضوري) في تعزيز الثقافة المقاولاتية لدى متربصي المعهد الوطني المتخصص في التكوين المهني المسيلة 02 متوسطة. هذا وأوصت الدراسة بضرورة إقامة علاقة تعاون وشراكة مع المؤسسات الصغيرة ومع الأفراد الذين حققوا نجاحا في حياتهم العملية. إضافة إلى خلق فضاءات تكوينية للشباب والمتكونين الراغبين في تأسيس مقاولات. الكلمات المفتاحية: التكوين المهني، متربصي التكوين المهني ، المقاولاتية، الثقافة المقاولاتية. Summary : The current study aimed to know the degree of contribution of vocational training: - organizational climate for vocational training - activities accompanying vocational training - applied internships in the professional environment )Attendance style( in promoting the entrepreneurial culture, and to achieve the objectives of the descriptive study, the researcher designed a questionnaire for this, and the study sample reached (95) consisting from different disciplines at the level of the National Institute specialized in vocational training in M’sila 02, and the study reached the following results:  The degree to which the organizational climate of vocational training contributes to the promotion )Attendance style( of entrepreneurial culture the trainees of the National Institute specialized in vocational training M’sila 02 is medium.  The degree to which the activities accompanying vocational training contribute to the promotion )Attendance style( of the entrepreneurial culture the trainees of the National Institute specialized in vocational training M’sila 02 is high.  The degree of contribution of applied internships in the professional environment to the promotion )Attendance style( of entrepreneurial culture the trainees of the National Institute specialized in vocational training M’sila 02 is medium. The study recommended the need to establish a relationship of cooperation and partnership with small enterprises and with individuals who have achieved success in their working lives. In addition to creating training spaces for young people and constituents wishing to establish businesses. Keywords : vocational training, vocational training trainees, entrepreneurship, entrepreneurial culture.